Analisis Faktor-Faktor Determinan yang Mempengaruhi Kualitas Audit - Lisa Aulia Julica; Rozie Meidy (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The purpose of this study was to determine the determinant factors that influence audit quality at the Inspectorate Office of North Musi Rawas Regency. The research method used is quantitative research where each variable is measured by a Likert scale. The number of samples in this study were 40 respondents. Data collection techniques used in this study were document studies and questionnaires. The data analysis technique uses multiple linear regression with the help of SPSS. The results of the study show that auditor competence has a significant influence on audit quality, this is evidenced by the results of the t-test calculation which shows a significance. Organizational commitment has a significant influence on audit quality, this is evidenced by the results of the t-test calculation which shows a significance. Auditor experience has a significant influence on audit quality, this is evidenced by the results of the t-test calculation which shows a significance. Work motivation has a significant influence on audit quality, this is evidenced by the results of the t-test calculation which shows a significance.